Ceny transferowe w praktyce przedsiębiorstw wielonarodowych - studium przypadku - Makowska, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The problem of transfer pricing is connected with a conscious and consequent reduction of political and economic barriers accompanying the globalization of companies' economic operations. The method of transfer price determination constitutes an important question in the internal settlements of companies. The paper presents the summary of an interview which has been conducted with a financial director of company X. It constitutes a part of the author's original research and its full scope has been presented in her masters thesis. The goal of the conducted interview was obtaining information on the transfer pricing policy used by the multinational company. The information presented in the paper concentrates on the following issues: general rules and requirements regarding the determination of transfer prices in company X, formulas used in the construction of transfer prices, factors determining the transfer pricing policy and its control by the tax administration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 198-219